Analysis of Factors Affecting Learning Outcomes Citizenship in Cadets Class IV West Sumatra Shipping Polytechnic - Fitri Mulyana; Neviyarni S (Postgraduate School, Universitas Negeri Padang, 2022)
This study aims to determine the factors that influence the learning outcomes of Citizenship in Cadets of the West Sumatra Shipping Polytechnic. The research method used is qualitative, a qualitative research method can be interpreted as a type of research based on the philosophy of postpositivism. Data collection techniques used were interviews, questionnaires, and documentation. With the research subject of Cadets Batch IV of the West Sumatra Shipping Polytechnic. Data analysis used in this study includes data collection, data reduction, data display, and conclusion. The results of the analysis show that internal and external factors affect the learning outcomes of Cadets' citizenship. Internal factors that influence consist of interest, motivation, and talent. while the external factors that influence consist of family factors and facilities and infrastructure factors.